Unemployment, inquality and the policy of Europe: 1984-2000 - Galbraith, James K.; Garcilazo, Enrique (PSL Quarterly Review, 2012)
This paper reconsiders the problem of unemployment in Europe at multiple geographic levels and through time from 1984 to 2000. We employ a panel structure that permits us to separate regional, national and continental influences on European unemployment. Important local effects include the economic growth rate, relative wealth or poverty, and the proportion of young people in the labor force. As part of this analysis, we assess the relationship between pay inequality and unemployment in Europe, following the insight of Harris and Todaro (1970) that pay inequalities influence job search. With our own panel of inequality measures derived from Eurostat's REGIO data set, we find that higher pay inequality, though usually taken to indicate greater labor market flexibility, is associated with more, not less, unemployment. Among large countries distinctive effects at the national level are few, perhaps indicating that national labor market institutions are not a decisive factor in the determination of unemployment. Changes in the macro-environment are picked up by time fixed effects, and these show a striking pan-European rise in unemployment immediately following the Maastricht Treaty, though with some encouraging recovery late in the decade. JEL Codes: E24, J31, J64